Stress-induced subsensitivity to catecholamines depends on the estrous cycle - Marcondes, F. K.; Vanderlei, L. C.M. [UNESP]; Lanza, L. L.B.; Spadari-Bratfisch, R. C. (My University, 1996)
In this article we compare how sensitivity to the chronotropic effect of noradrenaline and adrenaline of right atria isolated from female rats is modified after repeated swimming or foot-shock stress, under the influence of the estrous cycle. Right atria from stressed female rats sacrificed at diestrus were subsensitive to both catecholamines, irrespective of the stresser agent. However, although subsensitivity to noradrenaline was of similar intensity, subsensitivity to adrenaline was more pronounced in right atria from foot shock stressed rats as opposed to swimming-stressed rats. Identical stress protocols did not induce any alteration in atrial sensitivity to catecholamines when the stressed female rats were sacrificed at estrus. We conclude that the stress reaction concerning the mediation of cardiac chronotropism by catecholamines is related to the severity of the stresser agent and is strongly influenced by the estrous cycle.
Keywords: Adrenaline; Diestrus; Estrus; Female rats; Foot-shock stress; Noradrenaline; Swimming stress